The Malaysian Baba pantun database - Ding, Choo Ming (Universiti Kebangsaan Malaysia, 2004)
It is interesting to note that baba nyonya in the Straits Settlements managed to develop a body of literature using Romanized Malay by the end of the 1890s. In doing so, they independently started a Sino-Malay literary movement, a few years after their cousins in Java had done the same thing. This paper introduces the Baba Pantun database, comprising 11,204 pantuns, syairs and dondang sayang written and published by them in 35 books and newspapers from 1899 to 1940s